A qualitative study to identify critical attributes and attribute-levels for a discrete choice experiment on oral pre-exposure prophylaxis (PrEP) delivery among young people in Cape Town and Johannesburg, South Africa - Janan J. Dietrich; Millicent Atujuna; Gugulethu Tshabalala; Stefanie Hornschuh; Mamakiri Mulaudzi; Michelle Koh; Nadia Ahmed; Richard Muhumuza; Andrew S. Ssemata; Kennedy Otwombe; Linda-Gail Bekker; Janet Seeley; et al. (BMC, 2021)
Abstract Background The uptake and adherence of daily oral PrEP has been poor in high-risk populations in South Africa including young people. We used qualitative research methods to explore user preferences for daily and on-demand oral PrEP use among young South Africans, and to inform the identification of critical attributes and attribute-levels for quantitative analysis of user preferences, i.e. a discrete choice experiment (DCE). Methods Data were collected between September and November 2018 from eight group discussions and 20 in-depth interviews with young people 13 to 24 years in Cape Town and Johannesburg. Using a convenience sampling strategy, participants were stratified by sex and age. Interviewers used a semi-structured interview guide to discuss several attributes (dosing regimen, location, costs, side effects, and protection period) for PrEP access and use. Group discussions and in-depth interviews were audio-recorded, transcribed verbatim and translated to English. We used framework analysis to explore context-specific attributes and attribute-levels for delivering oral PrEP in South Africa. The adolescent community advisory board, expert and study team opinions were consulted for the final DCE attributes and levels. Results We enrolled 74 participants who were 51% (n = 38/74) male, had a median age of 18.5 [Interquartile range = 16-21.25] years, 91% (n = 67/74) identified as heterosexual and 49% (n = 36/74) had not completed 12th grade education. Using the qualitative data, we identified five candidate attributes including (1) dosing regimen, (2) location to get PrEP, (3) cost, (4) route of administration and (5) frequency. After discussions with experts and the study team, we revised the DCE to include the following five attributes and levels: dosing regime: daily, and on-demand PrEP; location: private pharmacy, public clinic, mobile clinic, ATM); cost: free-of-charge, R50 (~2GBP), R265 (~12GBP); side effects: nausea, headache, rash; and duration of protection: fulltime protection versus when PrEP is used). Conclusions There is limited literature on qualitative research methods describing the step-by-step process of developing a DCE for PrEP in adolescents, especially in resource-constrained countries. We provide the process followed for the DCE technique to understand user preferences for daily and on-demand oral PrEP among young people in South Africa.